’n Nederlandse vrywilliger by die Boere op kommando, 1899-1902: Hendrik ver Loren van Themaat en die Afrikaner (Historia, 2021)
This article examines jurist Hendrik ver Loren van Themaat's (1874-1966) experiences as a Dutch volunteer in the Boer forces during the Anglo-Boer War of 1899-1902, and more specifically his views on the Afrikaner. He arrived in Pretoria in December 1899, and subsequently did duty at the head office of the Transvaal Red Cross in Pretoria and in the commissariat on the Natal front, before joining the commandos as a combatant in February 1900. He was a member of Commandant Danie Theron's Scouting Corps, and accompanied the commandos under General Christiaan de Wet in all three so-called De Wet hunts. At the end of April 1902 he was back in Holland and published his memoirs in Dutch, based on his diary, in the following year. Aspects that are covered in the article are Ver Loren van Themaat's views on the Boer leaders, characteristics of the Afrikaner, Afrikaans as a language, and Afrikaner-Dutch relations. Although strongly pro-Boer with a great appreciation of the better qualities of the Afrikaner, he does not shy away from the weaker qualities. Ver Loren van Themaat was a great believer in the future of the Afrikaner, and he emigrated to South Africa in 1920. He was responsible for laying firm foundations for Constitutional and International Law at the University of Stellenbosch.
Keywords: Boer leaders; Jurists, Scouting Corps; Wassenaar; Ver Loren van Themaat, H.; Dutch volunteers; Anglo-Boer War; Afrikaners; Bilateral Conference Historians of the Netherlands and South Africa 2000; History